FGFR3 mutation frequency in 324 cases from the International Skeletal Dysplasia Registry - Xue, Yuan (Mol Genet Genomic Med, 2014)
Fibroblast growth factor receptor 3 (FGFR3) is the only gene known to cause achondroplasia (ACH), hypochondroplasia (HCH), and thanatophoric dysplasia types I and II (TD I and TD II). A second, as yet unidentified, gene also causes HCH. In this study, we used sequencing analysis to determine the frequency of FGFR3 mutations for each phenotype in 324 cases from the International Skeletal Dysplasia Registry (ISDR). Our data suggest that there is a considerable overlap of genotype and phenotype between ACH and HCH. Thus, it is important to test for mutations found in either disorder when ACH or HCH is suspected. Only two of 29 cases with HCH did not have an identified mutation in FGFR3, much less than previously reported. We recommend testing other mutations in FGFR3, instead of just the common HCH mutation, p.Asn540Lys. The mutation frequency for TD I and TD II in the largest series of cases to date are also reported. This study provides valuable information on FGFR3 mutation frequency of four skeletal dysplasias for clinical diagnostic laboratories and clinicians.